ASSOCIATION COVID-19 VIRAL LOAD AND DISEASE SEVERITY: A SYSTEMATIC REVIEW - Effendy, Kgs. Mahendra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The global pandemic SARS-CoV-2 or COVID-19 has caused a significant healthcare crisis. This disease profile is recognized as the leading cause of severe disease in the adult population and the focus of the evidence and treatment guidelines reflect that adults predominately experience COVID-19. A high temperature, a dry cough, dyspnea, headache, tiredness, loss of taste and/or smell, and gastrointestinal difficulties are among the symptoms of COVID-19. The results of the laboratory tests indicate that the levels of liver enzymes are elevated, that there is a shortage of lymphocytes (also known as lymphocytopenia), and that there is an increased level of C-reactive protein. The infection will, in the long run, cause acute respiratory distress syndrome, which could lead to death in the end. The reverse transcription-polymerase chain reaction (RT-PCR) was the single most essential tool for detecting the amounts of viral load. The identification of viral nucleic acid by RT-PCR assays is the gold standard for the diagnosis of COVID-19. This is because these tests can detect minute traces of the virus. We are able to obtain an indirect number for the viral load (C t) following the diagnosis using this procedure, which enables us to do so in a way that is both speedy and painless. The primary theory may be explained by the connection between the amount of viral load and inflammatory factors, both of which are obviously associated with the degree to which the disease has progressed. This connection may be explained by the correlation between the degree to which the disease has progressed and the amount of viral load. Because elderly patients typically have a higher viral load, it is possible that any potential links between COVID19 viral load and the severity of the disease could be explained by the fact that elderly patients often have a higher viral load.